Effectiveness of positive allosteric modulators of metabotropic glutamate receptor 2/3 (mGluR2/3) in animal models of schizophrenia - David Olivares-Berjaga; Albert Martínez-Pinteño; Natalia Rodríguez; Sergi Mas; Constanza Morén; Eduard Parellada; Patricia Gassó (Translational Psychiatry)
Abstract Schizophrenia (SZ) is a deleterious brain disorder characterised by its heterogeneity and complex symptomatology consisting of positive, negative and cognitive deficits. Current antipsychotic drugs ameliorate the positive symptomatology, but are inefficient in treating the negative symptomatology and cognitive deficits. The neurodevelopmental glutamate hypothesis of SZ has opened new avenues in the development of drugs targeting the glutamatergic system. One of these new therapies involves the positive allosteric modulators (PAMs) of metabotropic glutamate receptors, mainly types 2/3 (mGluR2/3). mGluR2/3 PAMs are selective for the receptor, present high tolerability and can modulate the activity of the receptor for long periods. There is not much research in clinical trials regarding mGluR2/3 PAMs. However, several lines of evidence from animal models have indicated the efficiency of mGluR2/3 PAMs. In this review, focusing on in vivo animal studies, we will specifically discuss the utilization of SZ animal models and the various methods employed to assess animal behaviour before summarising the evidence obtained to date in the field of mGluR2/3 PAMs. By doing so, we aim to deepen our understanding of the underlying mechanisms and the potential efficiency of mGluR2/3 PAMs in treating SZ. Overall, mGluR2/3 PAMs have demonstrated efficiency in attenuating SZ-like behavioural and molecular deficits in animal models and could be useful for the early management of the disorder or to treat specific subsets of patients.